Media Crime Prevention Campaign in the United States, 1980 - Mendelsohn, Harold ([Verlag nicht ermittelbar], 1984)
This data collection evaluated the effects of the "Take a Bite Out of Crime" public service advertising campaign. It sought to determine whether mass communications contribute to motivating the public to participate in crime prevention activities, and in what way the media could forge effective public communications on behalf of crime prevention. Variables cover perceptions and fear of crime, media use, sources of information about crime, and protective measures taken to prevent crime.